Puzzles of Destiny and the Constructs of Free Time: A New Historicist Reading of Written POWs’ Testimonials in WWII - Huljev, Antonija; Živić, Tihomir (Anafora, 2024)
In the paper, individual prisoners’ destinies and their free time are culturally reconstructed through comparative epistolographic analysis and Greenblattian New Historicist reading of authentic texts by British, Croatian, New Zealand, German, Italian, and Serbian POWs in American, German, and Italian POW camps during WWII. Decoding the comparative historical context proves the undying faith in freedom and the unyielding spirit manifested by the social games, concerts, (censored) camp publishing, theatrical performances, sports competitions, and even teaching, or carpentry and farming activities that were organized in the camps. Since, within a broader scope of POWs’ free time, camp correspondence can be scientifically studied as an important literary medium that also has a pronounced culturohistorical and educational role, the aforementioned methodology specifically describes, comprehends, and interprets the literal meanings and symbolic subtexts of the transcripts of eight authentic, hitherto publicly unavailable, POW letters and postcards. These transcripts, which highlight the general values promoted by the POWs, originate from one American, two German, and one Italian camp. Although the paper does not describe the specific conditions in each camp in detail, the texts of the analyzed letters and postcards, individual descriptions of daily life in a camp—that is, the POWs’ concern for their families and longing for their homes—can therefore, as the documents of time, also serve as credible data and educational material.